Annihilator of a Direct Sum: Proving V0=U0⊕W0 for V=U⊕W

In summary, it appears that the homework statement is incorrect, and that the correct conclusion is that V^*=U^0\oplus W^0.
  • #1
Adgorn
130
18

Homework Statement


Suppose V=U⊕W. Prove that V0=U0⊕W0. (V0= annihilator of V).

Homework Equations


(U+W)0=U0∩W0

The Attempt at a Solution


Well, I don't see how this is possible. If V0=U0⊕W0, then U0∩W0={0}, and since (U+W)0=U0∩W0, it means (U+W)0={0}, but V=U⊕W, so V0={0}. I don't think this is the desirable result so it means I misunderstood something along the way, clarification would be appreciated.
 
Physics news on Phys.org
  • #2
Adgorn said:
(U+W)0=U0∩W0
This part is not relevant. It is not the case that ##V=U+W##. We have ##V=U\oplus W## which has a different meaning.

To get a better handle on this, think about the following: say ##u\in U^0-\{0_U\}##. What is a corresponding element of ##V## that is in ##V^0##? Then do the same for ##w\in W^0-\{0_W\}##.
 
  • #3
Adgorn said:
Suppose V=U⊕W. Prove that V0=U0⊕W0. (V0= annihilator of V).
that is wrong.
the correct conclusion must be ##V^*=U^0\oplus W^0##
Indeed,
1) it is clear that ##U^0\cap W^0=\{0\}##; it also follows from
Adgorn said:
(U+W)0=U0∩W0

2) take any function ##f\in V^*## and define a linear function ##f_U## is follows ##f_U(x):=f(x)## provided ##x\in U## and ##f_U(x)=0## provided ##x\in W##;
similarly ##f_W(x):=f(x)## provided ##x\in W## and ##f_W(x)=0## provided ##x\in U##.
Obviously it follows that ##f=f_U+f_W,\quad f_U\in W^0,\quad f_W\in U^0##
 
Last edited:
  • Like
Likes Adgorn
  • #4
andrewkirk said:
This part is not relevant. It is not the case that ##V=U+W##. We have ##V=U\oplus W## which has a different meaning.

To get a better handle on this, think about the following: say ##u\in U^0-\{0_U\}##. What is a corresponding element of ##V## that is in ##V^0##? Then do the same for ##w\in W^0-\{0_W\}##.
But V=U⊕W means V=U+W and U∩W={0}, meaning the theorem still applies, doesn't it?
Also I am not familiar with the notation 0u and 0w, so i'd appreciate an explanation about that.
 
  • #5
zwierz said:
that is wrong.
the correct conclusion must be ##V^*=U^0\oplus W^0##
Indeed,
1) it is clear that ##U^0\cap W^0=\{0\}##; it also follows from

2) take any function ##f\in V^*## and define a linear function ##f_U## is follows ##f_U(x):=f(x)## provided ##x\in U## and ##f_U(x)=0## provided ##x\in W##;
similarly ##f_W(x):=f(x)## provided ##x\in W## and ##f_W(x)=0## provided ##x\in U##.
Obviously it follows that ##f=f_U+f_W,\quad f_U\in W^0,\quad f_W\in U^0##
Well this does make sense, if it is indeed a misprint in the book it would not be the first one...
 
Back
Top